Revolving Marriage Among the Radicals: An Analysis of Rotational Unrecorded Matrimonies within the Jemaah Islamiyyah Community - Al Chaidar, Al Chaidar; Faisal, Faisal; Sari, Elidar (De Jure: Jurnal Hukum dan Syari'ah, 2024)
This article examines the practice of revolving marriage among the members of Jemaah Islamiyyah (JI), a clandestine radical Islamist group in Southeast Asia. Revolving marriage is a term coined by the author to describe the phenomenon of JI members marrying and divorcing multiple partners in a short span of time without registering their marriages with the state authorities. Employing the ethnographic method, this article argues that revolving marriage serves as a strategy of survival, resistance and recruitment for JI, as it enables them to evade detection, foster solidarity and attract new followers. This research reveals how such practices are rooted in a multicultural Fiqh perspective, reflecting the movement's adherence to traditional values while navigating a diverse cultural landscape.